Why is physics hard? Unpacking students' perceptions of physics. (April 2020) - Bray, A; Williams, J
Abstract: It has been well established that there are many challenges associated with physics teaching and learning. This pilot study attempted to identify the perceptions of first-year students studying physics at Rhodes University in 2017. Academics in the Department were interviewed, a questionnaire was created and a survey was conducted with first-year students. Emotional issues were identified as the largest contributing factor to students' perceptions of physics. A high correlation between study skills and students' understanding and problem-solving abilities was observed. Under-preparedness was recognised as an important issue that needs further investigation.